Halal tourism: travel motivators and customer retention. Issue 9 (22nd November 2019) - Han, Heesup; Al-Ansi, Amr; Koseoglu, Mehmet Ali; Lin, Pearl M. C.; Park, Jinah; Yu, Jongsik; Kim, Wansoo
ABSTRACT: This research was designed to identify halal-friendly travel motivation factors and unearth their role in Muslim customer retention process in Korea. Qualitative and quantitative procedures were used to achieve research objectives. A comprehensive structural model was developed to distinguish the role of all proposed indicators. Our results revealed that halal-friendly travel motivations are significantly associated with customer return on investment and satisfaction, and that such relationships contribute to improving customer retention. The effectiveness of higher-order structure of halal-friendly travel motivations was demonstrated. The formation of Muslim customers' post-purchase decisions was significantly moderated by the sense of belonging to a tourist destination.